A high flexibility all-solid contact sulfide selective electrode using a graphene transducer. Issue 24 (9th June 2020) - Ye, Xiangyi; Qi, Peng; Sun, Yan; Zhang, Dun; Zeng, Yan
Abstract : In this paper, a novel high flexibility all-solid contact ion selective electrode (ASC-ISE) based on reduced graphene sheets (RGSs) as the ion-to-electron transducer was developed for rapid detection of sulfide. Abstract : In this paper, a novel high flexibility all-solid contact ion selective electrode (ASC-ISE) based on reduced graphene sheets (RGSs) as the ion-to-electron transducer was developed for rapid detection of sulfide. A graphene layer was firstly electrodeposited on a flexible silver wire by direct reduction of graphene oxide, and nanostructured Ag2 S was then prepared as the selective membrane by electrodeposition. Scanning electrochemical microscopy was performed for the characterization of the morphological properties of the RGSs and Ag2 S membranes. The evaluation of the analytical performances, such as the linear range, selectivity, stability, and practical application, of the proposed ASC-ISEs for the rapid detection of sulfide was performed. The results showed that, the ASC-ISEs exhibited a linear relationship between the obtained potential signal and sulfide concentration in the range of 0.50 μM to 1.0 mM, with a detection limit of 0.18 μM. Moreover, the ASC-ISEs showed good selectivity towards sulfide over other common interfering ions, and maintained a stable electrochemical response over 7 days. These results demonstrated that graphene was a promising material as the ion-to-electron transducer layer in the development of ASC-ISEs for sulfide detection, and the results of practical applications in tap water and seawater samples showed that the ASC-ISEs held significant promise in a broad range of applications.